Records of the Charles Darwin Foundation : Logistics (Logistica) - Charles Darwin Foundation (1972)
This collection contains the records of the Beagle III, Beagle IV and Beagle V, which were boats owned and operated by the CDF.
This collection contains records from the Archivo Inactivo Permanente, L121-L124, including contracts, sailings, seguros (anchors or lines?), repairs, accident reports, the Beagle V accident and search.
Spanish and English
A folder-level inventory of this collection is available in the Traslado de Documentacion para Archivo Inactivo Permanente (Febrero 2000). Digital and paper copies of this document are available in the Library.